The effect of veteran's entrepreneurial leadership on entrepreneurial success in Malaysia - M. Napi, Hapzarizal (Australian Academy of Business and Social Sciences, 2015)
This paper examines the effect of veteran’s entrepreneurial leadership factors (e.g; strategic, motivational, personal and communicative) on entrepreneurial success in Malaysia. The theoretical underpinnings and methodology to examine the effect of veteran’s entrepreneurial leadership factors on entrepreneurial success also been discussed. The gap in theoretical and practise, also been highlighted in order to justify the significance of this study. The result shows that the entrepreneurial leadership factors such as strategic, personal and communicative are positively related to entrepreneurial success while the motivational factors are not positively related to entrepreneurial success. In addition, the contribution of this study to the progression of theories and literatures related with entrepreneurial leadership and entrepreneurial success, will also contribute to the practise for policy maker and Malaysian government respectively.